Prenatal Diagnosis and Genetic Analysis of 21q21.1–q21.2 Aberrations in Seven Chinese Pedigrees - Hu, Huamei; Zhang, Rong; Ma, Yongyi; Luo, Yanmei; Pan, Yan; Xu, Juchun; Jiang, Lupin; Wang, Dan (Frontiers in Genetics, 2021)
Background: Chromosome aberrations can contribute to human phenotype, phenotypic diversity and disease susceptibility, which makes genetic counseling difficult. Therefore, it is of great value to report the new cases associated with both a normal phenotype and clinical abnormalities. Methods: G-banding and SNP-array techniques were used to analyze chromosome karyotypes and Copy number variations (CNVs) in fetuses and their family members. Results: The fetuses and those of their family members showed nomal karyotypes in seven pedigrees. Here, we revealed that the fetuses of Pedigree 1, 2, 3, 4, 5 and 6 all carried matrilineal-inherited 21q21.1-q21.2 duplications ranging from 1Mb to 2.7Mb. However, none of the mothers had an abnormal phenotype. Only in Pedigree 7, the fetus carried an 8.7Mb deletion of 21q21.1-q21.2. Subsequent pedigree analysis showed that the fetus's mother, brother, and maternal grandmother all carried the deletion of this segment, but the phenotypes were normal. Conclusion: Our study first showed aberrations of 21q21.1-q21.2 in Chinese population. Clinical and genetic investigation on six different pedigrees, we consider that the duplication of 21q21.1-q21.2 may be a benign CNV. Similarly, we provide new evidence for the judgment of pathogenicity of the deletion of 21q21.1-q21.2, which may not be a pathogenicity variant.